Culture and leadership in a public university setting: implications for shared governance and change - Mills, Edward E., author; Kuk, Linda, advisor; Morgan, George, committee member; Strathe, Marlene, committee member; Scott, Malcolm, committee member (Colorado State University. Libraries, 2014)
Noting a lack of quantitative research on perceptions of culture, leadership and change in the shared governance environment of Higher Education, this study utilized the Organizational Culture Assessment Instrument (Cameron & Quinn, 2011) to measure current (now) and preferred cultural perceptions of faculty and administrative leaders. Additional questions focused on the shared governance leadership culture within higher education. To explore this topic, participants were asked to rate their perceptions of the shared governance culture on their campus by rating the level of collaboration, impact on change at their campus and type of impact (positive, negative or neutral). Findings indicated that faculty and administrative leaders are more alike than different. Both groups considered their current leadership cultures predominantly Clan (collaborative, value-driven and participatory) and Hierarchical (bureaucratic, rigid and slow to change). But these same leaders display significant differences in their cultural preferences. Both groups indicated they would prefer a culture that was a combination of Clan and Adhocracy (innovative, adaptable and responsive) and less hierarchical. This study challenges the predominate notion in the literature on shared governance which infers faculty and administrative leaders differ in their perceptions on leadership and change. The study calls for more empirical research on this topic which would include larger populations and more demographic information on participants; limitations in this study.
Keywords: education; leadership; governance